Similar clinical outcomes of biceps tenodesis with various kinds of fixation techniques: a systematic review. Issue 6 (25th October 2019) - Lohakitsathian, Chairit; Mayr, Felix; Mehl, Julian; Siebenlist, Sebastian; Imhoff, Andreas B
Abstract : Importance: There are many different ways to fix the long head of biceps (LHB) tendon to the proximal humerus but there is still no consensus about clinical outcomes on how each fixation technique relates to biceps tenodesis. Objective: The purpose of this review was to systematically review subjective outcomes, patient and physical driven and surgical complications following tenodesis of the LHB tendon comparing different fixation techniques. Evidence review: A systematic search for articles on the biceps tenodesis technique with reports of at least one in three aspect outcomes was carried out from January 2013 to November 2018. PubMed, Embase and the Cochrane Library were the databases used for the literature review. The different surgical methods were compared by the number of studies that had significantly improved mean postoperative scores compared with preoperative scores. Besides this, the means of postoperative subjective outcome (Visual Analogue Scale for pain), and patient and physical driven (American Shoulder and Elbow Surgeons Score and the Constant-Murley Score) scores were also reported. Additionally, the complication rate of each technique was evaluated. Findings: Fifty studies out of 761 were included. The interference screw fixation without tie over screw, interference screw fixation with tie over screw, single anchor suture, knotless anchor suture and soft tissue tenodesis techniques had more than one study that reported significant improvement in postoperative subjective, patient and physical driven scores compared with preoperative scores. There was no significant difference in clinical outcomes of the interference screw without tie over screw compared with the single anchor suture and interference screw with tie over screw techniques. Soft tissue tenodesis, single anchor suture and knotless anchor suture showed higher complication rates in comparison with other methods. Conclusion and relevance: All five techniques mentioned above (interference screw fixation without tie over screw, interference screw fixation with tie over screw, single anchor suture, knotless anchor suture and soft tissue tenodesis) provided significant improvement in subjective outcomes, and patient and physical driven outcomes compared with the preoperative status. The soft tissue tenodesis, single anchor suture and knotless anchor suture techniques showed higher complication rates in comparison with other methods. Level of evidence: Level IV.